1997
DOI: 10.1108/09556229710168261
|View full text |Cite
|
Sign up to set email alerts
|

Sewability of denim

Abstract: IntroductionFabric quality alone does not fulfil all the criteria for production of high quality garments. The conversion of a two-dimensional fabric into a three-dimensional garment involves many other interactions[1] such as selection of a suitable sewing thread, optimization of sewing parameters, ease of conversion of fabric to garment and actual performance of a sewn fabric during wear of the garment.The selection of sewing thread for a fabric depends on the dimensional and mechanical properties of the fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 7 publications
1
45
0
1
Order By: Relevance
“…Prior to this, Shimazaki et al [3] proposed the use of an empirical equation for calculating the seam slippage depending upon the sewing length, loading and the axis of loading. Behera et al [4] emphasized that the seam slippage is related to mechanical properties of fabric and seam threads. Gurarda et al [5] showed that the reduction of the weft density results in the increase of the seam slippage.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to this, Shimazaki et al [3] proposed the use of an empirical equation for calculating the seam slippage depending upon the sewing length, loading and the axis of loading. Behera et al [4] emphasized that the seam slippage is related to mechanical properties of fabric and seam threads. Gurarda et al [5] showed that the reduction of the weft density results in the increase of the seam slippage.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, excessively heavy fabrics can also cause seam pucker. According to research by Behera et al, 1 the weight of a denim fabric is one of the factors affecting the seam appearance; results showed that puckering consistently increased with an increase in the weight of denim fabric. When the sewing thread penetrates a heavy fabric, it introduces a very high contractive force.…”
Section: Fabric Weightmentioning
confidence: 88%
“…1 The appearance of a garment is affected by the quality of the fabrics used in its manufacture, as well as the factors determined by the technology and parameters of the garment manufacturing process. The selection and use of the processes and parameters can ultimately affect the garment appearance.…”
Section: Introductionmentioning
confidence: 99%
“…The sewing thread performance in terms of seam efficiency, pucker, slippage, and needle cutting index was determined by Behera, Chand, Singh, and Rathee (1997). In addition to this, the results were analyzed in the light of the dimensional and mechanical properties of the fabric, thread, and seam.…”
Section: Introductionmentioning
confidence: 99%